Plio-Quaternary history of the Turkish coastal zone of the Enez-Evros Delta: NE Aegean Sea - ALPAR, B. (Mediterranean Marine Science, 2001)
The Enez-Evros Delta, NE Aegean Sea, is located in one the most important wetlands in the world with its sandy offshore islands, abandoned channel mouths, sand-dunes, shoals, marshlands, saline lagoons and saltpans. It comprises very well developed sedimentary units and a prodelta lying on an older submarine delta. The present day elevations of the middle-late Pleistocene marine terraces indicate a regional tectonic uplift in the area. Due to lack of geophysical and bore hole data and partly due to its strategic position, the structural and stratigraphic features of the submarine extension of the delta are not known in detail. In this paper, Plio-Quaternary history of this delta and its submarine part on the Turkish shelf was explored by using high-resolution shallow reflection seismic profiles. The delta is formed by the alluvial deposits of the Enez-Evros River and shaped by their interaction with the sea. It takes place in front of a large and protected ancient bay which was filled rapidly over millennia. The sediments in the plateau off the river are principally pro-deltaic with muddy areas near the river mouths changing to muddy sand further out. The sea-level changes in Plio-Quaternary were characterised by three different seismic stratigraphic units on the folded Miocene limestone basement. In the late Pleistocene, the shelf area over an Upper Miocene basement was flooded during the Riss-Würm interglacial period, exposed in the Würm glacial stage, and flooded once again during the Holocene transgression.